Ab initio insight into the physical properties of MgXH3 (X = Co, Cu, Ni) lead-free perovskite for hydrogen storage application - Rehman Z.; Rehman M.A.; Rehman B.; Sikiru S.; Qureshi S.; Ali E.M.; Awais M.; Amjad M.; Iqbal I.; Rafique A.; Bibi S. (Springer, 2024)
Renewable energy systems are vital for a sustainable future, where solid-state hydrogen storage can play a crucial role. Perovskite hydride materials have attracted the scientific community for hydrogen storage applications. The current work focuses on the theoretical study using density functional theory (DFT) to evaluate the characteristics of MgXH3 (X = Co, Cu, Ni) hydrides. The structural, vibrational, electronic, mechanical, thermodynamic, and hydrogen storage properties of these hydrides were investigated. The equilibrium lattice parameters were calculated using the Birch-Murnaghan equation of state-to-energy volume curves. The elastic constants (Cij) and relevant parameters, such as Born criteria, were calculated to confirm the mechanical stability of the hydrides. The Cauchy pressure (C p) revealed brittle or ductile behavior. The outcomes of the Pugh ratio, Poisson ratio, and anisotropy were also calculated and discussed. The absence of negative lattice vibrational frequencies in phonon dispersion confirmed the lattices dynamic stability. The heat capacity curves of thermodynamic properties revealed that hydrides can conduct thermal energy. The metallic character and ample interatomic distances of hydrides were confirmed by the band structure and population analysis, which confirmed that hydrides can conduct electrical energy and adsorb hydrogen. The density of state (DOS) and partial DOS unveiled the role of specific atoms in the DOS of the crystal. The calculated gravimetric hydrogen storage capacity of MgCoH3, MgCuH3, and MgNiH3 hydrides was 3.64, 3.32, and 3.49wt%, respectively. Our results provide a deeper understanding of its potential for hydrogen storage applications through a detailed analysis of MgXH3 (X = Co, Cu, Ni) perovskite hydride material. 2023, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.